KEJADIAN HIV/AIDS DENGAN MANIFESTASI ORAL PADA ANAK-ANAK - Nuzulul Hikmah; I Dewa Ayu Ratna Dewanti (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2010)
Nowadays HIV/AIDS infection was increase to children in the world. In development countries include Indonesia, it was caused fourth killer to children. Oral manifestation to the children who has infected HIV have a different been compared with adult. Discussion.Candidiasis and necrotizing ulcerative gingivitis is oral lesion who was found in the children. Linear gingival erythema leukoplakia, caries and kaposis sarcoma can be an indicator of moderate and hard immunosupression. Parotis swollen, herpes simplex virus infection and recurrent aphtous stomatitis not special connected with immunosupression grade. The best of management patients was consider immunology status andexamined oral continuity. Conclusion. Oral manifestation in the childen very important to known because it was often first indication clinical so that someone had been infected of HIV.